2001
DOI: 10.1182/blood.v98.9.2714
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transferrin receptor 2 in normal and neoplastic hematopoietic cells

Abstract: Iron is essential for cell proliferation, heme synthesis, and a variety of cellular metabolic processes. In most cells, transferrin receptor-mediated endocytosis is a major pathway for cellular iron uptake. Recently, transferrin receptor 2 (TfR2), another receptor for transferrin, was cloned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 19 publications
3
93
1
3
Order By: Relevance
“…Previous studies have suggested that TFR2 is expressed in erythroid cells [14] and is regulated by erythroid-specific transcription factors in vivo [15]. GWAS have suggested a correlation between the TFR2 genomic region and various hematological traits [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that TFR2 is expressed in erythroid cells [14] and is regulated by erythroid-specific transcription factors in vivo [15]. GWAS have suggested a correlation between the TFR2 genomic region and various hematological traits [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the liver, Tfr2 expression was also detected in the BM and early erythroid progenitors [14] with expression decreasing with cell differentiation [14]. Real-time PCR analysis revealed that Tfr2 expression begins between day 8 and 11 of embryonic development, which coincides with the time when primary hematopoietic cells move from the yolk sac to the liver for initial hematopoiesis [15].…”
Section: Introductionmentioning
confidence: 99%
“…TfR2 is highly expressed in the liver (22). There is some evidence that it is expressed in early erythroid precursor cells (21); however, this is controversial (1). Our recent studies (35) suggest that liver-expressed TfR2 plays a predominant role in the regulation of iron metabolism.…”
mentioning
confidence: 97%
“…15 As a further level of complexity, the TFR2 gene, which has two consensus sequences for the erythroid transcription factor GATA-1 in its promoter, 12 is expressed in immature erythroid cells 16 where it is a component of the erythropoietin receptor (EPOR) complex. 17 The TFR2-EPOR association is required for the efficient transport of EPOR to the cell surface.…”
mentioning
confidence: 99%